Prevalence and changes in food-related hardships by socioeconomic and demographic groups during the COVID-19 pandemic in the UK: A longitudinal panel study - Jonathan Koltai; Veronica Toffolutti; Martin McKee; David Stuckler (Elsevier, 2021)
Background: Food insecurity concerns have featured prominently in the UK response to the COVID-19 pandemic. We assess changes in the prevalence of food-related hardships in the UK population from April to July 2020. Method: We analysed longitudinal data on food-related hardships for 11,104 respondents from the April-July 2020 waves of the Understanding Society COVID-19 web survey with linked data from the 2017-9 wave of the annual Understanding Society survey. Outcome variables were reports of being hungry but not eating and of being unable to eat healthy and nutritious food in the last week, which were adapted from the Food Insecurity Experience Scale. We used unadjusted estimates to examine changes in population prevalence and logistic regression to assess the association between employment transitions and both outcomes at the individual level. Findings: The prevalence of reporting an inability to eat healthy or nutritious food rose from 3•2% in April to 16•3% in July 2020. The largest increases in being unable to eat healthy or nutritious food were among Asian respondents, the self-employed, and 35-44-year-olds. The prevalence of being hungry but not eating rose from 3•3% in April to 5•1% in July, with the largest increases observed among unemployed individuals below age 65. Those moving from employment to unemployment had higher odds of being hungry but not eating in the last week relative to furloughed individuals (OR = 2•2; p < 0•05; 95% CI: 1•1 to 4•2) and to the persistently employed (OR = 3•5; p < 0•001; 95% CI: 1•8 to 6•9), adjusting for age, highest qualification in 2017-19, net household income in 2017-19 (equivalized), gender, race/ethnicity, number children at home (aged 0-4, 5-15, and 16-18), cohabitation status, and government office region. Respondents moving from employment to unemployment also had higher odds of reporting an inability to eat healthy and nutritious food relative to furloughed individuals (OR = 1•9; p < 0•05; 95% CI: 1•4 to 3•2) and to the persistently employed (OR = 2•0; p < 0•01; 95% CI: 1•2 to 3•4). No statistically significant differences were found between furloughed individuals and the persistently employed in their probability of reporting either outcome. Interpretation: Food-related hardships increased substantially in the UK between April and July 2020, largely driven by reports of an inability to eat healthy and nutritious food. The Coronavirus Job Retention Scheme and Self-Employment Income Support Scheme appeared to have conferred some protection, but more could have been done to mitigate the problems we describe in obtaining affordable food. Funding: DS is funded by the Wellcome Trust investigator award. JK and DS are funded by the European Research Council n. 313590 - HRES. VT is funded by the European Research Council n. 694145- IFAMID.